ORTHODONTIC MARVEL: 2X4 APPLIANCE FOR IMPACTED INCISOR TRACTION - A CASE SERIES - SIMRAN ISHA; Sonal Gupta; Menia Gumro (International Journal of Medical Research and Review, 2023)
Impacted incisors can pose significant esthetic and functional challenges for patients. Various treatment approaches have been proposed. The 2x4 orthodontic appliance is one of the most effective treatment plans for aligning the teeth. This article presents two cases showing surgical traction's effectiveness using the 2x4 orthodontic appliance in managing impacted incisors. The results of this case series demonstrated successful outcomes in terms of impacted incisor alignment and overall occlusion. Patients exhibited improved esthetics and function. Therefore, Surgical traction of impacted incisors using the 2x4 orthodontic appliance can be a viable and effective treatment approach.